Application of The Single Index Model In The Establishment of A Portfolio Stock Optimization - Siti Aisyah; Hamidah Nasution (UIN Sumatera Utara, 2021)
Investing in stocks in the capital market is an investment that has big risks, so if you are not careful in choosing stocks, it can cause losses. In this case, investors need to form an optimal portfolio of shares to reduce risk in investment activities in the capital market. The purpose of this study was to determine the optimal portfolio value of stocks during the COVID-19 pandemic using a single index model. The data used are stock price data, the JCI and the BI Rate, which is from January to December 2020. Based on the research that has been done, 6 stocks are classified into the optimal stock portfolio during the 2020 pandemic. The proportion value of each share is COCO shares of 0.84%, GOOD shares are 59%, ROTI shares are 35%, SKBM shares are 0.78%, ULTJ shares are 1.4%, and UNVR shares are 3%, with an expected portfolio return value of 0.39% and a risk of 0.0066%.